A Comparative Study on Fish and Macrofaunal Diversity of the Koshi River Near Madhepura, Bihar - Yadav, Bhagwat (RESEARCH HUB International Multidisciplinary Research Journal, 2026)
Koshi River also referred to as the Sorrow of Bihar is one of the most dynamic river systems of the eastern part of the Indo-Gangetic plains and is significant to the maintenance of aquatic biodiversity as well as the livelihoods of the locals. The current paper presents a detailed analysis of fish and macrofauna community of Koshi River close to Madhepura, Bihar, and attempts to examine the ecological state and determine the effect of hydrological and anthropogenic conditions on the diversity trends of biodiversity. The braided streams, periodic flooding, high sediment loads and extensive floodplain wetlands are the features of the river that produce heterogeneous habitats which sustain diverse ichthyofauna and macrofauna. The diversity of fish was determined as being relatively high with 25-45 species representing over eight families and mainly Cypriniformes, especially the major Indian carps such as Labeo rohita which is the mainstay of the local fisheries. Macrofaunal diversity that includes fishes, freshwater prawns (Macrobrachium spp.), and mollusks (Pila, Lamellidens) was more sensitive to environmental stress, but taxonomically broader. The seasonal change had a very strong impact on biodiversity with the highest level of fish diversity during the monsoon and post-monsoon seasons because of the connectivity of the floodplain and the greatest macrofaunal diversity in winter when the river flow was in stasis and the turbidity was low (diversity index = 1.47). This paper has noted the growing dangers of overfishing, habitat destruction, pollution, and river management, and the necessity of combined conservation policies, sustainable fisheries management policies, and habitat conservation policies. The results give the necessary background information on ecosystem-based management and long-term conservation planning in the lower Koshi basin.